2007
DOI: 10.1620/tjem.212.283
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to the High Cesarean Section Rate and Their Effects on the "Price Transparency Policy" in Beijing, China

Abstract: In urban China, many non-clinically indicated cesarean sections (NCSs) are performed, resulting in an unnaturally high cesarean section (CS) rate. NCSs represent CSs without any specific medical indications. The demand for NCS may be due to women's preference for CS and their belief in its safety and comfortableness. In addition, CS is more profitable for the supply side than vaginal delivery, which results in a continued rise in delivery expenditures. As a result, the so-called "price transparency policy", wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 15 publications
(20 reference statements)
2
44
0
Order By: Relevance
“…Unfortunately, this measure did not achieve its goal. 26 Professional bodies in China lack the power to ensure best practices; it is up to individual doctors and medical department heads to uphold medical and ethical principles in standard care. Furthermore, until WHO's global survey showed that China had the highest caesarean section rate in the South-East Asia Region, academic groups and professionals had focused primarily on preventing the complications of caesarean section rather than on preventing …”
Section: Researchmentioning
confidence: 99%
“…Unfortunately, this measure did not achieve its goal. 26 Professional bodies in China lack the power to ensure best practices; it is up to individual doctors and medical department heads to uphold medical and ethical principles in standard care. Furthermore, until WHO's global survey showed that China had the highest caesarean section rate in the South-East Asia Region, academic groups and professionals had focused primarily on preventing the complications of caesarean section rather than on preventing …”
Section: Researchmentioning
confidence: 99%
“…According to the National Health Services Survey (China Ministry of Statistics, 2004), among all pregnant women who delivered infants in mainland China, 20% in the rural areas and more than 63% in the urban areas were admitted to general hospitals. A strong technological influence has developed, and midwives are involved in task-oriented situations in general hospitals with little time is available for psychological and individualized support (Hong, 2007). The study was carried out in one general hospital, a leader in providing obstetric services in Guangzhou, where about 3,000 babies are delivered per year.…”
Section: Samplementioning
confidence: 99%
“…1,[7][8][9] Between 1990 and 2002, the rate among primiparous women living in cities in China rose from 18% to 39% 8 and close to two thirds of urban women now give birth by caesarean section. [10][11][12] Although the rate in rural China has risen more slowly, it is now thought to be above 25%. 9,13,14 Opinions differ on why the rate has risen so rapidly in China.…”
Section: Introductionmentioning
confidence: 99%
“…On the demand side, women may request a caesarean section because they fear the consequences of vaginal delivery. 10,12,[15][16][17] When having one child is the norm, rich and well educated women may prefer birth by caesarean section to vaginal delivery because they think it is safer and free from pain and anxiety. 12,[15][16][17] More evidence for this reasoning comes from the high proportion of indications for caesarean section categorized as "woman's request" or "due to social factors" in hospital records 10,12,[15][16][17] and from the persistently higher rates observed among rich and well educated women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation